(untitled) (Research, Society and Development, 2022)
Objective: to evaluate coping coping strategies of nursing workers at a university hospital. Method: cross-sectional study carried out in 2018 with 67 nursing workers. To assess coping strategies, the Occupational Coping Scale was used. Results: most were cis-gender women, single, with a mean age of 39.1 years, nursing technicians and working the day shift, and the population presented the coping process through a control coping strategy (average of 3, 58). Conclusion: that knowledge about coping strategies favors the management of human resources, early detection of problems related to the work environment, in addition to the prevention of risks to workers and promotion of occupational health.